Comparative analysis of ATC probabilistic methods - Hojabri, Mojgan; Hizam, Hashim; Mariun, Norman; Abdullah, Senan Mahmood (Marsland Press, 2010)
The price of power transfer between two areas is a key issue between buyers and sellers in the power market which is directly related to the ATC deal and security. ATC deal is computed by Deterministic methods and ATC security presented by probabilistic methods. Since the ATC is used for operation or planning of power system, ATC can be determined by Deterministic or Probabilistic methods. In this paper, existing probabilistic methods which could predict ATC for power system planning are reviewed and compared.